Training on the Preparation of Madrasah Operational Curriculum (Kom) Kkma Pringgabaya-Sambelia - Mahsur, Mahsur; Rabiatul Hasanah , (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The independent curriculum is a new policy initiated by the minister of education. Madrasah must be ready to face change. Responding to these changes, madrasas need to gain knowledge related to the independent curriculum and the preparation of the Madrasah Operational Curriculum (KOM) which is in line with national education goals. This research aims to increase the capacity of madrasah teachers in compiling the Madrasah Operational Curriculum (KOM) based on Freedom of Learning. Through intensive workshop activities, madrasah teachers in Pringgabaya-Sambelia District were given training on the basic principles of the Independent Curriculum and practical steps in compiling KOM. The results showed a significant increase in participants' understanding of the concept of Freedom of Learning and their ability to design more flexible and student-centered learning. However, this study also identifies a number of challenges faced by teachers in implementing the Independent Curriculum, such as limited resources and resistance to change. Therefore, continuous efforts are needed to provide support and assistance to teachers in this curriculum transformation process. Overall, this study highlights the importance of the role of teachers in the successful implementation of the Independent Curriculum. By increasing the capacity of teachers in compiling KOM, it is hoped that the quality of learning in madrasas can be improved and the goal of Freedom of Learning to create creative, critical, and independent graduates can be achieved.